Effect of hot blanching / cooking on the survival of Listeria monocytogenes in Penaeus indicus - Jeyasekaran, G; Karunasagar, Indrani; Karunasagar, Iddya (Indian Journal of Fisheries, 2011)
The effect of hot blanching / cooking on the survival of Listeria monocytogeneswas studied. Fresh shrimp specimens (Penaeus indicus) were peeled and inoculatedwith L. monocytogenes (NCTC 1994) at a level of 105 cfu /g. The inoculatedshrimps were subjected to hot blanching / cooking at 1000C for 2 min, cooledimmediately and stored at refrigerated temperatures. L. monocytogenes survivedupto 7 days of storage. The findings indicate that L. monocytogenes exhibitsheat tolerance and consumption of inadequately cooked contaminated shrimpmay lead to listeriosis